2016
DOI: 10.1007/s00270-016-1426-y
|View full text |Cite|
|
Sign up to set email alerts
|

Unresectable Hepatocellular Carcinoma: Radioembolization Versus Chemoembolization: A Systematic Review and Meta-analysis

Abstract: TARE appears to be a safe alternative treatment to TACE with comparable complication profile and survival rates. Larger prospective randomized trials, focusing on patient-reported outcomes and cost-benefit analysis are required to consolidate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 39 publications
3
112
0
2
Order By: Relevance
“…Moreover, although not explicitly stated, a 3‐year survival time is usually defaulted to be an important watershed for the prognosis of unresectable HCC patients treated with TACE. And, many previous studies utilized “3 year” as an important time point to report the accordingly survival rate in HCC patients treated with TACE . Therefore, based on the previous studies and data in the current study, we considered “3 years” as a reasonable (clinically, statistically, and empirically) cutoff value indicating the long‐term survival in HCC patients undergoing TACE.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, although not explicitly stated, a 3‐year survival time is usually defaulted to be an important watershed for the prognosis of unresectable HCC patients treated with TACE. And, many previous studies utilized “3 year” as an important time point to report the accordingly survival rate in HCC patients treated with TACE . Therefore, based on the previous studies and data in the current study, we considered “3 years” as a reasonable (clinically, statistically, and empirically) cutoff value indicating the long‐term survival in HCC patients undergoing TACE.…”
Section: Discussionmentioning
confidence: 98%
“…However, when PVT or risk of ischemia is present TARE, PEI, or IRE are preferred modalities. These modalities are also limited by their availability, high cost, and operator experience …”
Section: Discussionmentioning
confidence: 99%
“…The patient treated with TACE needs at least one day of hospital stay, while TARE is an outpatient procedure. 154 In another meta-analysis by Zhang Y et al, different results were observed. They believed that TARE with Yttrium-90 had better OS, TTP and lower hospitalization time over TACE .…”
Section: Chemotherapy and Radiotherapymentioning
confidence: 97%